Radicalism in Ali Jinnah's Land, Religion or Group Matters? - Alauddin, Muhammad Badat; Zuhair, Rofi Hamzah; Al-Haidary, Abdullah Haq (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This article examines the issue of radicalism in Pakistan, often identified as the